Celebrate Ramadan & Eid al-fitr - Heiligman, Deborah; Yavari, Neguin (Washington, D.C. : National Geographic, 2006)
Presents the history of the Islamic holiday month of Ramadan and its ending celebration Eid al-fitr and describes the activities associated with them.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references.
Notable Children's Trade Books in the Field of Social Sciences (2007).
Description based on print version record.
Keywords: Ramadan -- Juvenile literature; v; Fasts and feasts -- Islam -- Juvenile literature; Islam -- Rituals -- Juvenile literature; Ramadan; Electronic books- OSLIS; Electronic books